Faktor pembangunan dan kemunduran pengajian sains Islam silam - Alias Bin Azhar, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2010)
The present form of Science and modern technology is threatening the Islamic authority. In fact its form is not from that in Islamic scientific tradition which is part and parcel of the civilization. However we need to depend on the present form of science and technology. This has implication to ward our understanding and interpretation of Islam if we want to understand the problems faced by Muslim in this modern world. But, the apparent conflict between Islam and modern science can be overcome through cautiously analyzing and studying the criteria and nature of traditional Islamic science. A qualitative study and historical analysis were adopted as core methods of study and had produced convincing outcome. Development factors and past Islamic science developement were found to be due to both internal and external factors. We should examine factors as they can be used as guidelines in our effort to realize the Malaysian mould of science development. The finding of this analysis, although important cannot replace the modern science and its implications. It can however be applied towards the construction of a framework or mould required to help us understand and overcome the problems faced when there appear to be a clash between Islam and modern science.